The brain and behavior an introduction to behavioral neuroanatomy - Clark, David L. 1939- (Cambridge University Press, 2010)
Now in its third edition, The Brain and Behavior continues on its mission to present a simplified and accessible introduction to behavioral neuroanatomy. Human behavior is a direct reflection of the anatomy of the central nervous system, and it is the goal of the behavioral neuroscientist to uncover its neuroanatomical basis. Much of the new content in this edition reflects advances in functional magnetic resonance imaging. The text is presented in a highly structured and organized format to help the reader distinguish between issues of anatomical, behavioral and physiological relevance. Simplified and clear diagrams are provided throughout the chapters to illustrate key points. Case examples are explored to set the neuroanatomy in the context of clinical experience. This will be essential reading for behavioral clinicians including psychiatrists, neuropsychiatrists, neurologists, psychologists and clinical neuroscientists